PENILAIAN KERUSAKAN DAN KERUGIAN INFRASTRUKTUR PUBLIK AKIBAT DAMPAK BENCANA BANJIR DI KOTA SEMARANG - Ilham Sahid Wismana Putra; Ferry Hermawan; Jati Utomo Dwi Hatmoko (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2020)
Flood is a disaster that has the biggest threat, in terms of the number of victims or losses. Semarang City is a city that is classified as a flood prone area, this is due to the geographical location in the lowlands and highlands. The impact of the flood disaster caused damage and losses from various sectors of public infrastructure including the education service sector and health services. Damage and loss of public infrastructure will burden the government in the post-flood recovery phase. An assessment of infrastructure damage and losses from flooding is needed in order to help the Semarang City Government prepare a budget plan and manage rehabilitation and reconstruction. The purpose of this research is to explore the loss of public infrastructure due to the impact of the flood disaster, so that it can accelerate the post-disaster recovery process and management strategies for the risk of further flood disasters. The valuation method used is ECLAC (Economic Commission for Latin American and the Caribbean) Method. This method can identify damage and estimate the losses caused by floods. The results of this study are that each public infrastructure building has a different level of damage and loss and the budget allocation for disaster management each year is still inadequate. A risk transfer strategy is needed with an insurance financing scheme based on the level of risk in each infrastructure building.